2006
DOI: 10.1111/j.1095-8649.2006.01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of latitude, water depth, dayv.night and wetv.dry periods on the species composition of reef fish communities in tropical Western Australia

Abstract: Trap sampling over reefs in deep (mean ¼ 20 m) and shallow (mean ¼ 10 m) waters along c. 1500 km of coastline in tropical north-western Australia during both day and night and in wet and dry periods yielded 23 377 fishes, representing 32 families, 58 genera and 119 species. Individuals of the Serranidae, Lutjanidae, Lethrinidae and Carangidae contributed 88Á9% to the total catch. The ichthyofaunal compositions of the Kimberley, Canning and Pilbara bioregions were relatively discrete. Species composition was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…This is consistent with the results of previous trapping studies Williams, 1995, 2001;Travers et al, 2006). Carpenter and Allen (1989) reported that most species of lethrinids feed at night, but recognize that many species 'forage coincidentally or purposefully during the day'.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the results of previous trapping studies Williams, 1995, 2001;Travers et al, 2006). Carpenter and Allen (1989) reported that most species of lethrinids feed at night, but recognize that many species 'forage coincidentally or purposefully during the day'.…”
Section: Discussionsupporting
confidence: 92%
“…Some authors found that amount of living hard coral cover was positively related with fish species richness (Carpenter et al 1981;Bell and Galzin 1984;Cadoret et al 1999) whereas others recorded no such relationship (Luckhurst and Luckhurst 1978;Roberts and Ormond 1987;Lecchini et al 2003). Most recently, the spatial structure and distribution of fish assemblages have been related to water depth (Russ 1984a;Fowler 1990;Friedlander and Parrish 1998;Cadoret et al 1999;Lecchini et al 2003), exposure (Williams 1982;Victor 1986;Depczynski and Bellwood 2005), reef zone (Lecchini et al 2003;Depczynski and Bellwood 2005), distance from the shoreline to offshore waters (Williams 1982;Green et al 1987;Adjeroud et al 1998;Lecchini et al 2003) and geographical location (Travers et al 2006). In general, findings from previous studies on relationships between the spatial distribution and structure of reef fish communities and environmental factors have provided conflicting conclusions.…”
mentioning
confidence: 92%
“…Habitat type and complexity are important determinants of the structure of fish assemblages (Friedlander and Parish, 1998;Almany, 2004;Travers et al, 2006Travers et al, , 2010Giakoumi and Kokkoris, 2013;Wakefield et al, 2013). Fish abundance, diversity and distribution has been shown to be positively correlated with the structural complexity of habitats, likely due to the additional refuge from predators and availability of resources (e.g.…”
Section: Introductionmentioning
confidence: 98%